Efektivitas Media Pembelajaran Bio Board Games Panjat Pinang Pada Materi Biologi Semester Genap Kelas XI SMA Negeri 6 Takalar - Agustina Agustina; Muhiddin Palennari; Firdaus Daud (Universitas Negeri Makassar, 2022)
Media has a very important role in the learning process. Media can be used as learning aids that can make it easier for teachers to convey material in the learning process while making it easier for students to receive and understand material with the media product of climbing areca nut bio board games. The purpose of this research is to produce a media product for the areca nut climbing board game for learning biology. This media serves as a tool to stimulate memory and strengthen material for class XI SMA/MA students. This research is a development research using the Borg and Gall model which consists of the stages of Research and Information collecting, planning, developing preliminary form a product, preliminary field testing, main product revision, main field testing. The sample of this study was students of SMAN 6 Takalar class XI MIPA 1 with a total of 36 respondents. This research was conducted in December 2021 – February 2022. The instrument developed for effectiveness was the learning outcome test instrument. The learning media of the areca climbing Bio Board Games has collaborative, competitive, and cooperative elements. The media of the areca climbing Bio Board games that was developed was then tested for validity until it was declared valid by the validator and then implemented to determine the effectiveness through a learning outcome test. The results showed that the learning media of the areca climbing bio board games which was developed especially on learning outcomes met the effectiveness criteria because the number of students who obtained complete scores at the time of the posttest (94.5%) was in the very good category and the average value of the analysis was N- the normalized gain of 0.69 is in the medium category. Thus, based on the score obtained, the media is declared feasible and effective for use in biology learning, especially in the material of the circulation system.